Triangular Energy-Saving Cache-Based Routing Protocol by Energy Sieving - Chiu-Ching Tuan; Yi-Chao Wu (International Journal of Distributed Sensor Networks)
In wireless ad hoc networks, designing an energy-efficient routing protocol is a major issue since nodes are energy limited. To address energy issue, we proposed a triangular energy-saving cached-based routing protocol by energy sieving (TESCES). TESCES offered a grid leader election by energy sieving (GLEES), a cache-based grid leader maintenance (CGLM), and a triangular energy-saving routing discovery (TESRD). In GLEES, only few nodes join in grid leader election to be elected as a grid leader. New grid leader is elected directly by cache without sending extra control packets in CGLM. TESRD selects an energy-efficient path to transmit data packets. Hence, TESCES could save more energy for transmitting packets and prolong routing lifetime. Simulation results showed that TESCES could reduce 31% of energy consumption, prolong 67% of routing lifetime, and increase 19% of survival ratio of nodes. Furthermore, TESCES may be more outstanding as the number of nodes increased.